Impact of spraying with Cycocel growth regulator and seaweed ex-tract in growth indicators for local oranges Citrus sinensis (L.) - Al-Hamdani, Haider Ali Abdul Hussein (Journal of Kerbala for Agricultural Sciences, 2023)
The carried experiment the nurseries located in the Al-Issa area and the wooden canopy / Kufa district in Al-Najaf Al-Ashraf governorate for the agricultural season 2022 to show the effect of spraying with the growth regulator Cycocel concentration (0, 1500, 11000, 11500) mg L-1 and spraying with seaweed extract (Super Fifty) At a concentration of (0, 0.25, 0.50, 0.75) ml L-1 and their interactions in the growth and vegetative characteristics of one-year-old Local orange seedlings grafted on orange rootstocks. The experiment was carried out Using (RCBD) according to the complete randomized block design, with 3 replications and (16) plants for each replicate. The individual results of two study factors and the interaction between them showed Positive superiority in seedling height, number of leaves, leaf area, the number of branches, and Leaf chlorophyll concentration total. Carbohydrate content in leaves in compared to the comparison (Control) treatment, as for stem diameter, it was not significant in all characteristics of both searches in a manner individually and intertwined.